Visible Dissent : Latin American Writers, Small U.S. Presses, and Progressive Social Change - Longo, Teresa, 1956- (New American canon., 2018)
As Teresa Longo's groundbreaking examination reveals, North America's dissident literature has its roots in the Latin American literary tradition. From Pablo Neruda's Canto General to Eduardo Galeano's Open Veins of Latin America to Gabriel García Márquez's One Hundred Years of Solitude--among others--contemporary writers throughout the Americas have forced us to reconsider the United States's relationship with Latin America, and more broadly with the Global South. Highlighting the importance of reading and re-reading the Latin American canon in the United States, Longo finds that literature can be an instrument of progressive social change, and argues that small literary presses--City Lights, Curbstone, and Seven Stories--have made that dissent visible in the United States. In the book's final two chapters on the Robert F. Kennedy Center's Speak Truth to Power initiative and the publication of Marc Falkoff's Poems from Guantánamo, the author turns our attention further outward, probing the role poetry, theater, and photography play in global human rights work. Locating the work of artists and writers alongside that of scholars and legal advocates, Visible Dissent not only unveils the staying-power of committed writing, it honors the cross-currents and the on-the-ground implications of humane political engagement.